Development of Employee Performance Management Application for Consumer Service Division in Apartments Using Extreme Programming Methodology - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
This research aims to develop an employee performance management application in the apartment customer service division using the Extreme Programming (XP) method. The initial research stage involved identifying user needs through interviews, surveys, and observations. Application development was carried out by designing prototypes, selecting technologies, and implementing key features with a focus on the XP method. The user acceptance analysis stage involved representative group testing to assess user experience and collect feedback. System testing included tests of functionality, user interface, integration, security, performance, device compatibility, disaster recovery, and user evaluation, all of which passed successfully. The results showed that the application could improve the efficiency and effectiveness of employee performance management in the customer service division. The conclusion states that the application is ready for implementation, positively contributing to performance management practices by effectively utilizing application technology. This abstract provides a concise overview of the research journey and critical findings, providing a basis for relevant parties to understand the contribution of this application in improving productivity and service quality.